Menginang Sirih dan Tradisi yang Hampir Hilang pada Masyarakat Banjar serta Perspektifnya dalam Kesehatan Gigi untuk Wujudkan Indonesia Bebas Karies 2030 - Topan Sulaiman Asy’ari; Riska Amelia Safitri; Nur Shofa Fhadila; Nidaul Jannah; Chintana Aurel Hairin; fauzie21@ulm.ac.id (Poltekkes Kemenkes Kendari, 2023)
Introduction: Dental health problems in Indonesia are still relatively high. Based on the 2018 Riskesdas results, the prevalence of caries in Indonesia reached 57.6%. In South Kalimantan Province, 46.90% of the population suffers from dental caries. One of the factors thought to be related to the prevalence of dental caries is the habit of